The Role of Motivation in Mediating the Effect of Transformational Leadership on Teacher Performance in Asti Dharma Foundation Primary Schools - Endang Ratma Wati Parhusip; Agus Wahyudin (Educational Management, 2026)
This study aims to analyze the role of motivation in mediating the influence of transformational leadership on teacher performance at Asti Dharma Foundation Elementary Schools. This study employs a quantitative approach with descriptive and causal designs. Data were collected through a closed-ended questionnaire using a 1–5 Likert scale to measure transformational leadership, teacher motivation, and teacher performance.The study population consisted of all elementary school teachers at the Asti Dharma Foundation, totaling 168 teachers from eight elementary schools. The sampling technique used was saturated sampling, in which the entire population was included as the study sample. Data collection was conducted by distributing questionnaires to respondents, and the data were analyzed using statistical methods to test direct and indirect relationships between variables.The results of the study indicate that transformational leadership has a positive and significant effect on teacher performance. Teacher motivation also has a positive effect on teacher performance. Furthermore, transformational leadership was found to enhance teacher motivation. This study also found that teacher motivation mediates the effect of transformational leadership on teacher performance. Thus, the implementation of effective transformational leadership and the enhancement of teacher motivation are crucial factors in improving teacher performance and the quality of education at Yayasan Asti Dharma Elementary School.